C-Peptide: A New Mediator of Atherosclerosis in Diabetes. (22nd March 2012) - Vasic, Dusica; Walcher, Daniel
Abstract : Diabetes type 2 and insulin resistance are the risk factors for cardiovascular disease. It is already known that atherosclerosis is an inflammatory disease, and a lot of different factors are involved in its onset. C-peptide is a cleavage product of proinsulin, an active substance with a number of effects within different complications of diabetes. In this paper we discuss the role of C-peptide and its effects in the development of atherosclerosis in type 2 diabetic patients.